BUILDING PERFORMANCE AND WORK MOTIVATION - Hunein, Hamida (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2018)
Every company has a purpose, the establishment of a company has a clear purpose. There are several things that suggest about the purpose of establishing a company. The company's first goal is to achieve maximum profit or profit as much as possible. The second goal of the company is to prosper the company owner or shareholders. The purpose of this research are: 1). to test and analyze the effect of training on employee performance at Sales Department PT. X. 2). to test and analyze the effect of incentives on employee performance at Sales Department PT. X. 3). to test and analyze the effect of supervision on employee performance at Sales Department PT. X. 4). to test and analyze the effect of training on motivation at Sales Department PT. X. 5). to test and analyze the influence of incentives on motivation at the Sales Department of PT. X. 6). to test and analyze the influence of supervision on motivation at the Sales Department of PT. X. 7). to test and analyze the effect of employee performance on motivation at Sales Department PT. X. The results of this study are: 1). there is influence of training on employee performance , with path coefficient 0,167 and tcount 2,015 with probability equal to 0,046 (0,046 <0.05). 2). there is influence of incentive on employee performance , with path coefficient 0,187 and tcount 2,293 with probability equal to 024 (0.024 <0.05). 3). there is an influence of supervision on employee performance , with path coefficient of 0403 and tcount of 5.004 with probability of 0.000 (0.000 <0.05). 4). there is influence of training on motivation , with path coefficient of 0.156 and tcount of 2,185 with probability of 0.031 (0.031 <0.05). 5). There is influence of incentive to motivation , with path coefficient 0,161 and tcount 2,260 with probability equal to 0.026 (0.026 <0.05). 6). there is influence of supervision to motivation , with path coefficient 0,350 and tcount 4,636 with probability equal to 0.000 (0.000 <0.05). 7). there is influence of employee performance to motivation , with path coefficient 0,314 and tcount 3,978 with probability 0,000 (0.000 <0.05)